DEVELOPMENT OF AN EVALUATION SYSTEM FOR PARKS IN NEIGHBORHOOD COMMUNITIES – CASE STUDY IN KITAKYUSHU CITY, JAPAN - Liyang Fan; Yui Konishi; Hidetoshi Fukahori; Weijun Gao; Zhu Wang (International Association of Lowland Technology, 2014)
Parks are an important aspect of an ideal city. In the “neighborhood development” concept, the public park is the core of a neighborhood block, which is one of the basic components of the city. Using the neighborhood parks in Kitakyushu, Japan, as a case study, this research proposes an evaluation system for parks in urban area. First, the study uses GIS to identify each neighborhood park and define the neighborhood community. It then classifies neighborhood parks according to the land-use pattern of their communities. Next, the study develops an assessment index and used it for principal component analysis. Finally, based on the results of the analysis, the study comprehensively evaluates the community and park system in Kitakyushu city, Japan. The findings suggest that comparative evaluation between the different parks can help in understanding the characteristics and problems of existing information.